Monogenoidea parasitos de brânquias de duas espécies de peixes dulcícolas da Bacia do Médio Rio Munim, Estado do Maranhão, Nordeste do Brasil - Silva, Marciara Lopes (2023)
Fish are remarkably sensitive to anthropic interference in their habitat, and can produce different responses to these stresses, as well as changes in the association pattern with parasites, which results in an imbalance in the parasites intensity per host, allowing interpretations on sanitary and ecological perspective. This work aimss to characterize the Monogenoidea parasite diversity of two freshwater fish species (Bryconops cf. affinis, and Crenicichla brasiliensis), which occur in the middle Munim River basin. In this study 64 individuals of each host species were collected using trawls and cast nets in tributaries of the middle Munim River, in the municipalities Chapadinha and Anapurus, eastern Maranhão, in the dry and rainy seasons. The captured fish were taxonomically identified at the Laboratory of Systematics and Ecology of Aquatic Organisms at the Federal University of Maranhão. The 128 hosts were euthanized by medullary section, and after the session of all muscle spasms, the gills were removed and conditioned in three parts of water heated to 70 ºC and seven parts of absolute ethanol, resulting in a concentration of ethanol 70%. The analysis and collection of ectoparasites was conducted at the LAMP - Immunohistochemistry Laboratory at the State University of Maranhão, and at UFMA partner laboratories. The Monogenoidea were obtained through a detailed analysis of the branchial arches, and mounted on slides containing Hoyer's medium for clarification and evidence of sclerotized structures, as well as the acquisition of microscopic images and species identification. The parasites belonged to two genera of Monogenoidea, where four species were identified: Diaphorocleidus affinis, Diaphorocleidus sp. n. 1 and Diaphorocleidus sp. n. 2 parasites of Bryconops cf. affinis; and Sciadicleithrum sp., parasite of Crenicichla brasiliensis. Seasonality influenced the occurrence of Monogenoidea, with the rainy season showing higher prevalence, average abundance, average intensity of infestation and amplitude of intensity. The occurrence of parasites was correlated with temperature (ºC) and dissolved oxygen (OD) in the rainy season for the two fish species analyzed. In this work, D. affinis is redescribed with new morphological data and new illustrations. Diaphorocleidus sp. n. 1 and Diaphorocleidus sp. n. 2 differ from all other congeners and are here proposed as two new species. Sciadicleithrum sp. also differs from its congeners, however, it needs further studies to confirm the species identification. In addition, the Munim River basin is a new geographical record for D. affinis. Considering the scarcity of conducted studies on the parasitic fauna of small-sized freshwater fishes, and the importance of the sustainability of the middle Munim River basin for the municipalities, the present research will contribute to the biomonitoring of the studied basin